Secretion of biologically active interferon-gamma inducible protein-10 (IP-10) by Lactococcus lactis - Villatoro Hernández, Julio; Loera Arias, María de Jesús; Gámez Escobedo, Idalia Analí; Franco Molina, Moisés Armides; Gomez Gutierrez, Jorge G; Rodríguez Rocha, Humberto; Gutiérrez Puente, Yolanda; Saucedo Cárdenas, Odila; Valdés Flores, Jesús; Montes de Oca Luna, Roberto (2008)
Background: Chemokines are a large group of chemotactic cytokines that regulate and direct migration of leukocytes, activate inflammatory responses, and are involved in many other functions including regulation of tumor development. Interferon-gamma inducible-protein-10 (IP-10) is a member of the C-X-C subfamily of the chemokine family of cytokines. IP-10 specifically chemoattracts activated T lymphocytes, monocytes, and NK cells. IP-10 has been described also as a modulator of other antitumor cytokines. These properties make IP-10 a novel therapeutic molecule for the treatment of chronic and infectious diseases. Currently there are no suitable live biological systems to produce and secrete IP-10. Lactococcus lactis has been wellcharacterized over the years as a safe microorganism to produce heterologous proteins and to be used as a safe, live vaccine to deliver antigens and cytokines of interest. Here we report a recombinant strain of L. lactis genetically modified to produce and secrete biologically active IP-10. Results: The IP-10 coding region was isolated from human cDNA and cloned into an L. lactis expression plasmid under the regulation of the pNis promoter. By fusion to the usp45 secretion signal, IP-10 was addressed out of the cell. Western blot analysis demonstrated that recombinant strains of L. lactis secrete IP-10 into the culture medium. Neither degradation nor incomplete forms of IP-10 were detected in the cell or supernatant fractions of L. lactis. In addition, we demonstrated that the NICE (nisin-controlled gene expression) system was able to express IP-10 "de novo" even two hours after nisin removal. This human IP-10 protein secreted by L. lactis was biological active as demonstrated by Chemotaxis assay over human CD3+T lymphocytes. Conclusion: Expression and secretion of mature IP-10 was efficiently achieved by L. lactis forming an effective system to produce IP-10. This recombinant IP-10 is biologically active as demonstrated by its ability to chemoattract human CD3+ T lymphocytes. This strain of recombinant L. lactis represents a potentially useful tool to be used as a live vaccine in vivo.